Compliance com os requisitos de divulgação do IFRS - International Financial Reporting Standards e sua relação com o erro de previsão dos analistas de mercado - Silva, Flávia Almeida Morato da (2015)
The objective of this study is to make an econometric analysis of the relationship between analysts’ earnings forecast errors and firm compliance with the disclosure requirements of IFRS (International Financial Reporting Standards). This was done through a panel data methodology of the analysts’ earnings forecast errors on IFRS implementation year in Brazil (2010) and, complementary, in 2012, in order to reference this data. Based on this assumption, the forecast error of the companies listed on the BM&FBOVESPA S.A. (Bovespa) was determined with earnings’ forecast of earnings and the earnings observed (earnings ratio per share / earnings per share) which are available on the databases I / B / E / S Earnings Consensus Information provided by Thomson ONE Investment Banking and Economática Pro®, respectively. We find a negative relationship between forecast errors and compliance with the IFRS disclosure requirements, thus higher quality of disclosed information leads to a lower error forecast of analysts. Therefore, these results support the idea that the compliance level of accounting standards is so or more important than the standards themselves. Furthermore, when company listed on the BM&FBOVESPA is linked to a Regulatory Agency, we evaluated that its analysts’ earnings forecast does not change. Lastly, is important to improve the audit mechanisms to encourage the compliance of firms with legal requirements, such as enforcement, corporate governance structures and internal and external audits